An aspect of neolithisation in Mongolia - Séfériades, Michel Louis (Documenta Praehistorica, 2004)
The article outlines the first results of the French Archaeological Mission to Mongolia centered on the Neolithic. The topics discussed include general aspects of the initial Neolithisation in Eurasia, and the use of state-of-the art archaeological techniques in studies of Prehistory, with special reference to the Mesolithic/Neolithic interface, as exemplified by a survey and excavations in the area of Tamsagbulag site (Eastern Mongolia, aimak/district of Dornod) originally investigated by a Soviet-Mongolian mission directed by Professor A. P. Okladnikov, a renowned Russian archaeologist.
Keywords: arheološka najdišča; arheološke najdbe; prazgodovina; mezolitik; neolitik; Mongolija